Fundamental study on brain signal for bci-fes system development - A. Rahman, K. A.; Ibrahim, B. S. K. K.; Leman, A. M.; A. Jamil, M. M. (2012)
Electroencephalographic measurements are commonly used in medical and research areas. This article presents an introduction into Electroencephalography (EEG) measurement and the simple experiment of EEG. Its purpose is to develop orientation in EEG field and with building basic knowledge for performing EEG recordings. The normal person used as subject was used in this experiment. It is conducted in three condition; relax, hand grasp and lastly grasp and release. At the end of the experiment, there are some changes of the brain signal due to the activity that subject has been done. It shows that the brain will generate the different signal relate to the activity or the way of thinking of the subject. This study will be used as a fundamental concept for Brain Computer Interface (BCI)- Functional Electrical Stimulation (FES) system development.